Improving the Physico-mechanical Properties of Extruded Rice Based on Mixed Rice-quinoa Flours Using Pickering Emulsion-filled Gel Containing Beta-carotene - Maryam Davtalab; Sara Naji-Tabasi; Mostafa Shahidi (مجله پژوهش‌های علوم و صنایع غذایی ایران)
IntroductionRice is a strategic product and considered as staple food of over half of the world's population particularly in Iran. Considering the high levels of rice waste, including broken grains or those of lower quality, it can be utilized for producing value-added foods and reducing waste. Extrusion is a process widely used to improve food products and develop fortified foods. Quinoa flour is rich in phenols, and can be utilized to produce fortified extruded rice. The extrusion of gluten free flours like rice and quinoa has different challenges. In this study, sodium alginate was used to prepare emulsion filled gel to enhance the stability of Pickering emulsions containing β-carotene and also structuring rice during extrusion process. Pickering emulsion is one of the encapsulation methods suitable for encapsulating lipophilic compounds like β-carotene. Emulsion-filled gels, developed using hydrocolloid mixtures, significantly enhance emulsion stability and make them suitable for aqueous food environments. Finally, extruded rice based on a mixture of rice- quinoa flours and fortified with beta-carotene was prepared, and its physico-mechanical properties were evaluated.Materials and MethodsPickering emulsions were stabilized using whey protein- cress gum soluble complex nanoparticles. Beta-carotene was dissolved in the oil phase at a concentration of 0.1%. Subsequently, 4% (w/v) sodium alginate was used to develop emulsions filled-gel.The Pickering emulsion was dispersed in the sodium alginate gel at a ratio of 15:85. Extruded rice was then prepared using an equal ratio (50:50) of broken rice flour and quinoa flour via a cold extruder. To evaluate the impact of the gel-filled emulsion on improving the characteristics of rice grains, different concentrations (30%, 35%, and 40% w/w) of the gel-filled emulsion (based on flour weight) were added to the mixture. The physico-mechanical tests (moisture content, ash content, optimum cooking time, water absorption ratio, cooking loss, lateral expansion, textural characteristics of rice, color properties, sensory analysis, structural morphology, Beta-carotene stability) were conducted. Duncan test was utilized to identify statistically significant differences (p<0.05) among the means, while one-way analysis of variance (ANOVA) was employed to investigate the impact of various factors. Results and DiscussionThe incorporation of emulsions filled-gel into quinoa-rice blend significantly influenced the physico-mechanical properties of extruded rice. As the concentration of emulsions filled-gel increased from 30% to 40% (w/w), there was a significant increase in moisture content, ash content, expansion ratio, and cooking time. Extruded rice samples with emulsion-filled gel exhibited significantly greater β-carotene stability than those without, both after cooking and during storage. Conversely, adhesiveness decreased while hardness increased with increasing emulsion filled-gel concentrations. The control sample exhibiting the highest adhesiveness and lowest hardness. The lightness of the extrudates was also improved with increasing emulsion filled-gel levels, reaching a maximum at 40% (w/w). Sensory evaluation revealed that the 40% emulsion filled-gel level was the most preferred sample by panelists. The optimized extruded rice closely resembled natural Hashemi rice in terms of sensory and textural properties.ConclusionThe findings of this study demonstrate that the addition of emulsions filled-gel enriched with beta-carotene can effectively enhance the physico-mechanical properties of extruded quinoa-rice blends. Specifically, increasing the emulsion concentration resulted in improving expansion, textural, and appearance properties of the rice. 40% emulsion filled-gel was found to be optimal, resulting in a product with desirable sensory attributes. This research proposes that extruded rice based on mixed rice-quinoa flours enriched with beta-carotene-loaded emulsion-filled gel can provide a nutritious and appealing alternative to broken rice products, leveraging the nutritional benefits of quinoa. Sensory and textural evaluation revealed that the extruded rice exhibited sensory properties highly similar to natural Hashemi rice, coupled with favorable cooking characteristics. Consequently, it can be introduced as a suitable substitute for natural rice.